Making Website-Based of Promotional Media Using CMS Wordpress at Eltabo Coffee in Cimahi - Silvia Kesia Christina Aritonang; Maya Setiawardani (Ebiz Prima Nusa, 2023)
Technological advances that are happening at this time are of benefit to many groups, one of which is businessman. Advances in technology make it easy for businessman to market their products or services. As a result of this convenience, many UMKM have sprung up, including in Cimahi City. Many new businesses have started to emerge including coffee shops or cafes. The many appearances of these coffee shops make the competition even tighter. Eltabo Coffee, which is located in Cimahi City, is one of the new coffee shops. Intense competition and the foreign name Eltabo Coffee among the people of Cimahi City, caused Eltabo Coffee to experience a decline in income. To overcome these problems, this Final Project was made with the aim of knowing how the initial conditions of promotional media from Eltabo Coffee, to find out how to make website-based promotional media using CMS WordPress, and to find out the results of implementing website-based promotional media on Eltabo Coffee using CMS WordPress. The implementation of this project applies the SDLC method which consists of the planning, analysis, design, and implementation stages. The results of making this website-based media promotion show a very good value, namely an assessment of the website from the owner of Eltabo Coffee as well as from the results of the questionnaire. In addition, there were 9 new customers who visited Eltabo Coffee Cimahi after visit the Eltabo Coffee website and there was an increase in sales in the second and third weeks of May, namely 23 cups. Trials by the admin have been carried out by changing photos on the Menu page.